2010
DOI: 10.1108/00035591011009673
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐dyes as corrosion inhibitors for mechanically pretreated aluminum

Abstract: Purpose -The purpose of this paper is to provide acid-dyes, known for the dyeing of porous aluminum oxide films, as inhibitors of the corrosion of aluminum in neutral chloride solutions. Design/methodology/approach -Potentiodynamic polarization plots are recorded on mechanically pretreated aluminum using a three-electrode cell containing 0.01 M NaCl solution with or without 0.025 mM of the acid-dyes monosulfonic methyl orange (MO), disulfonic chromotrop RR (CH), disulfonic alphazurine A (AZ) and trisulfonic li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Li et al studied the inhibition effect of crystal violet (CV) on the corrosion of cold-rolled steels in 1.0 M HCl solution and found that it is an excellent inhibitor [ 14 ]. Careful examination of the data reveals that triphenylmethane dyes can block the active sites of corrosion and reduce the corrosion current density, thereby inhibiting the corrosion of metal in hydrochloric acid [ 15 , 16 , 17 ]. Despite numerous studies on dyes as corrosion inhibitors, the performance of triphenylmethane dyes in CO 2 corrosion remains unexplored, which represents a novel direction for corrosion research.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al studied the inhibition effect of crystal violet (CV) on the corrosion of cold-rolled steels in 1.0 M HCl solution and found that it is an excellent inhibitor [ 14 ]. Careful examination of the data reveals that triphenylmethane dyes can block the active sites of corrosion and reduce the corrosion current density, thereby inhibiting the corrosion of metal in hydrochloric acid [ 15 , 16 , 17 ]. Despite numerous studies on dyes as corrosion inhibitors, the performance of triphenylmethane dyes in CO 2 corrosion remains unexplored, which represents a novel direction for corrosion research.…”
Section: Introductionmentioning
confidence: 99%
“…In study [31], xylenol orange was tested as a corrosion inhibitor for aluminum in trichloroacetic acid. In study [32], with a variety of dyes, methyl orange was used as a corrosion inhibitor for mechanically pretreated aluminum. Yet another study [33] used methyl orange as a dye adsorbed onto films of anodized aluminum oxide for pH sensing purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Although methods for modifying the aluminum surface by anodizing and further processing are known [23,24,27,28,32,33,36,37], such tests have not been performed on recycled alloy 6082. This article shows practical examples of surface treatment of 6082 alloy: solid and its scrap.…”
Section: Introductionmentioning
confidence: 99%